Limitations imposed on land properties resulting from the construction and exploitation of transmission devices in Poland - Sajnóg, Natalia; Sobolewska-Mikulska, Katarzyna (International Conference “Environmental Engineering”, 2017)
Sustainable social and economic development of the country, as well as the need to ensure its energy safety requiresthe modernisation of the existing and construction of new transmission devices. The characteristic feature of technical infrastructure is its linear nature, i.e. its course through numerous real estates, resulting in limitations imposed on such properties. The limitations differ depending on the stage of the investment process. Such stages include the formal legal stage (designing and collecting appropriate permits and decisions), the investment implementation stage, and the stage of exploitation of transmission devices. Within the first stage, a limitation concerning land development may occur (location of investments in planning documents); limitations of the use of land properties always occur in this case (acquisition of a legal title to the land property disposal for building purposes). At the stage of construction, i.e. the investment implementation, limitations related to the deterioration of the use of the land property may appear. The third stage may involve limitations connected with the presence of transmission devices in the space of the land property, i.e. limitations which result from the actual use of the land property by the transmission company. The objective of this paper is to identify limitations imposed on land properties resulting from the construction and exploitation of transmission infrastructure in Poland.